2023
DOI: 10.1002/ijc.34742
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of patient‐specific clinical features on osimertinib effectiveness in a real‐world cohort of patients with EGFR mutated non‐small cell lung cancer

Ard van Veelen,
G. D. Marijn Veerman,
Marjon V. Verschueren
et al.

Abstract: Osimertinib is prescribed to patients with metastatic non‐small cell lung cancer (NSCLC) and a sensitizing EGFR mutation. Limited data exists on the impact of patient characteristics or osimertinib exposure on effectiveness outcomes. This was a Dutch, multicenter cohort study. Eligible patients were ≥18 years, with metastatic EGFRm+ NSCLC, receiving osimertinib. Primary endpoint was progression‐free survival (PFS). Secondary endpoints included overall survival (OS) and safety. Kaplan‐Meier analyses and multiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
(127 reference statements)
0
5
0
Order By: Relevance
“…Patients included in the current study were previously described in other studies evaluating different research questions, but the specific question whether plasma levels are associated with BM outcomes was not evaluated. 18 , 19 , 20 , 21 We think that our study adds to the available literature. Furthermore, we did not use the proposed cutoff of C min 166 ng/mL, because we found that a large proportion of our patients had a C min above this value.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…Patients included in the current study were previously described in other studies evaluating different research questions, but the specific question whether plasma levels are associated with BM outcomes was not evaluated. 18 , 19 , 20 , 21 We think that our study adds to the available literature. Furthermore, we did not use the proposed cutoff of C min 166 ng/mL, because we found that a large proportion of our patients had a C min above this value.…”
Section: Discussionmentioning
confidence: 71%
“…This study was approved in each center (MUMC+; 2019-1080, NKI/AvL; IRBd19-192 and IRBdm20-218, ErasmusMC; 16-643, START-TKI; NCT05221372). Samples from patients included in this study were previously evaluated for other research questions by Van Veelen et al., 18 Agema et al., 19 Boosman et al., 20 and Veerman et al.. 21 All patients signed informed consent. Patients who underwent a dose reduction of osimertinib during treatment were excluded from the analyses, because the found plasma C min,SS would not be representative for the total time of osimertinib treatment.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations